2016
DOI: 10.3348/kjr.2016.17.4.509
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Multidetector CT and Gadobutrol-Enhanced MR Imaging for Evaluation of Small, Solid Pancreatic Lesions

Abstract: ObjectiveTo compare multidetector computed tomography (MDCT) and MRI for lesion conspicuity, as well as the detection and characterization of small solid pancreatic lesions (SPLs).Materials and Methods193 patients with small SPLs (< 3 cm) and 52 patients with normal pancreas who underwent both multiphasic MDCT and gadobutrol-enhanced MRI were included in our study. Two radiologists blinded to the pathologic diagnoses independently reviewed those images, and determined the detection of "SPL per se" and "SPL in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
0
10
0
1
Order By: Relevance
“…The sensitivity of gadobutrol-enhanced MRI for detecting small, (i.e. < 3 cm) solid pancreatic lesions (SPLs) was significantly higher than that with CT imaging in 193 patients with SPLs (98–99.5 vs. 91–93% ; p < 0.05) [ 49 ]. There was no significant difference between the two imaging techniques for the specificity of detecting SPL (100% for both techniques for both readers).…”
Section: Diagnostic Efficacy Of Gadobutrolmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of gadobutrol-enhanced MRI for detecting small, (i.e. < 3 cm) solid pancreatic lesions (SPLs) was significantly higher than that with CT imaging in 193 patients with SPLs (98–99.5 vs. 91–93% ; p < 0.05) [ 49 ]. There was no significant difference between the two imaging techniques for the specificity of detecting SPL (100% for both techniques for both readers).…”
Section: Diagnostic Efficacy Of Gadobutrolmentioning
confidence: 99%
“…There was no significant difference between the two imaging techniques for the specificity of detecting SPL (100% for both techniques for both readers). Overall, SPL were significantly ( p < 0.001) more conspicuous on gadobutrol-enhanced MRI than CT images [ 49 ].…”
Section: Diagnostic Efficacy Of Gadobutrolmentioning
confidence: 99%
“…MRI is more accurate than CT in the detection of small pancreatic adenocarcinoma and in liver staging. [ 29 31 ]…”
Section: Imaging Methodsmentioning
confidence: 99%
“…The detection of pancreatic adenocarcinomas is reported to be superior for Magnetic Resonance (MR) imaging with respect to CT [ 15 ]. Choi et al reported that MR was able to identify small PDAC better than CT [ 18 ] ( Table 2 ).…”
Section: Methodsmentioning
confidence: 99%